SISTEM PENDUKUNG KEPUTUSAN PEMBELIAN MOBIL BEKAS MENGGUNAKAN METODE SAW DAN TOPSIS - Jordhy Yacob Sterian Solukh; Gregorius Rinduh Iriane (Lembaga Pengembangan Kinerja Dosen, 2025)
Cars are one of the growing transportation in Indonesia. This is because cars have good comfort and safety. But many people cannot buy their dream car in a new condition because the price is still expensive, therefore buying a used car is an alternative to these limitations. However, in selling used cars, it is often difficult for consumers to compare which car is better and feasible, because they do not know what things to pay attention to in buying a used car so that it takes a long time to choose a car and seems less efficient. This research aims to develop a Decision Support System for buying used cars using the Simple Additive Weighting method and the Technique For Others Reference by Similarity to Ideal Solution method. The Simple Additive Weighting method is a method that can determine the weight of the value of each criterion, then can determine the ranking so that the best alternative can be selected from several alternatives. The Technique For Others Reference by Similarity to Ideal Solution method is a method where the selected alternative not only has the shortest distance from the positive ideal solution but also has the longest distance from the negative ideal solution. Thus, the system built can speed up the decision-making process in purchasing a used car.